STUDIES ON GENETIC PARAMETERS FOR ANAEROBIC GERMINATION TRAITS, YIELD AND ITS CONTRIBUTING CHARACTERS IN RICE (Oryza sativa L.) - S. NARENDER REDDY, E. UMARANI, V. HEMALATHA, L.V. SUBBARAO, C.N. NEERAJA SUNEETHA KOTA and (The Journal of Research, PJTSAU, 2019)
Rice is the most important cereal crop, which is the staple food for more than half of the world’s population. It has shaped the cultures, diets and economies of billions of people living in Asia where it has a long history of cultivation and is deeply ingrained in the daily lives of Asian people.